1965
DOI: 10.1002/bip.360030204
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of aminoacridines with deoxyribonucleic acid: Effects of ionic strength, denaturation, and structure

Abstract: SynopsisThe binding crirves of various arniiioacridines on calf thymiis DNA have been determined by a spectrophotometric method. The dominant role of electrostatic forces in the interaction has been confirmed by the effect of ionic strength. Side chain and ring sri1)stitiients in the amirioacridines do riot inhibit binding. since this decreases in the order: arrariil > neoniotiacriti > atebrin > !I-aminoacridineproflavine > Y-amino-1,2,3,4-tetrahydroacriditie (THA). The last named shows the effect, of diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1966
1966
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(24 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…In accordance with DNA-aminoacridine intercalation models which explain binding form one (Lerman, 1963;Drummond et al, 1965), the aminoacridine molecule still intercalates between successive nucleotide bases. AO, whose structure might render intercalation more difficult, is in this regard at a disadvantage when compared to PF.…”
Section: Interpretation Of the Different Effectiveness Of A 0 And Pfmentioning
confidence: 55%
“…In accordance with DNA-aminoacridine intercalation models which explain binding form one (Lerman, 1963;Drummond et al, 1965), the aminoacridine molecule still intercalates between successive nucleotide bases. AO, whose structure might render intercalation more difficult, is in this regard at a disadvantage when compared to PF.…”
Section: Interpretation Of the Different Effectiveness Of A 0 And Pfmentioning
confidence: 55%
“…He continued to study the structure of "naked" DNA but also started to work on DNA isolated from cells still wrapped in proteins that normally accompany it inside cells. Among the studies on "naked" DNA was the work that resulted in a long series of highly noted publications on the binding of various dyes to RNA and DNA, and the effects of such molecules on the structure, and in later works the function, of nucleic acids (Drummond, Simpson, et al 1965;Blake and Peacocke 1966;Drummond, Pritchard, et al 1966;Nicholson and Peacocke 1966;Pritchard, Blake, et al 1966;Blake and Peacocke 1967a, b;Blake and Peacocke 1968;Lloyd, Prutton, et al 1968;. Most of the dyes that Peacocke studied fit into the category known as DNA intercalating agents; such molecules bind specifically to DNA by fitting into the inner structure of the DNA double helix and find their way to fit into a space between DNA bases.…”
Section: Zygonmentioning
confidence: 99%
“…These observations suggested that the dye might modify the conformation of the polymer, but this was not observed directly (12). In (6).…”
mentioning
confidence: 95%